2022
DOI: 10.3390/plants11223016
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Humate and Plant Growth-Promoting Microbes Jointly Mitigate Water Deficit Stress in Soybean Cultivated in Salt-Affected Soil

Abstract: Lack of high-quality irrigation water and soil salinity are two main environmental factors that affect plant development. When both stressors are combined, the soil becomes sterile and constrains plant productivity. Consequently, two field trials were designed to assess whether plant growth-promoting microbes (PGPMs; Bradyrhizobium japonicum (USDA 110) and Trichoderma harzianum) and potassium humate (K-humate) can stimulate soybean growth, productivity, and seed quality under two different watering regimes as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…An assessment of the combined influences of humates and bacteria on the productivity of agricultural plants showed their greater effectiveness compared to the use of each of them separately [ 27 , 34 ]. To the best of our knowledge, the effect of a combination of humates and bacteria on woody plants was previously carried out only on pine and poplar seedlings [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…An assessment of the combined influences of humates and bacteria on the productivity of agricultural plants showed their greater effectiveness compared to the use of each of them separately [ 27 , 34 ]. To the best of our knowledge, the effect of a combination of humates and bacteria on woody plants was previously carried out only on pine and poplar seedlings [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the addition of potassium humate increases growth in wheat [39], aromatic plants [40], and in cotton plant fiber, it increases quality and productivity [41]. Potassium humate has proven to be effective to alleviate both salt stress in the common bean [42] and soybean [43], and arsenic toxicity in rice [44], but descriptions of its effect at the molecular level are scarce. Arabidopsis is a standard model system in plant biochemistry and molecular biology.…”
Section: Discussionmentioning
confidence: 99%
“…Our research showed that the combination treatment could increase soil microbial activity and activate soil enzymes, primarily dehydrogenase and nitrogenase. In general, the combination treatment has demonstrated a good effect in terms of stimulating plant development and raising elements concentrations in wheat and faba bean under salt stress.Similarly, Alharbi et al [12]concluded that the combined application of plant growth-promoting microbes (PGPMs; Bradyrhizobium japonicum (USDA 110) and Trichoderma harzianum) and potassium humate (K-humate) resulted in a substantial improvement in K+ levels in the leaves compared to Na + levels, which has a direct positive impact on an enhancement in the antioxidants defense system (CAT, POX, SOD), which caused the decline of the oxidative stress indicators (H2O2 , MDA, and EL%) as well as proline content that led to a significant increase in root length, nodule weight, soybean relative water content (RWC), stomatal conductance, photosynthetic pigments, net photosynthetic rate, soluble protein, seed carbohydrate content as well as the number of pods. plant −1 and seed yield.…”
Section: Effects Of Microbiomes and K-humate On Wheat And Faba Bean Y...mentioning
confidence: 90%
“…Although, PGPRs and HA in different agricultural systems have already stimulated these processes reduced salinity damage in some crops under controlled experimental conditions, the field effect was insignificant and did not reflect productivity gains. This demonstrates the need for field tests to validate the potential of these biostimulants under real planting conditions [12].Thus, the main challenge of the Egyptian farmers is to grow up salt-tolerant plants under such saline and alkaline conditions and also to manage the ameliorating inputs to lessen further soil deterioration while sustaining soil productivity. Keeping this in mind, lab and field experiments were conducted to study the ability of cyanobacteria, yeast and AMF, individually or in combination, as inoculants to ameliorate salinity stress and enhance productivity of faba bean (Vicia faba L.) and Wheat (Triticum aestivum L.) in presence of humic acids and stimulatory dose (25%) of the recommended mineral fertilizers.…”
Section: Introductionmentioning
confidence: 99%